Comparative Immune Response Pattern of Commercial Infectious Bursal Disease Vaccines Against Field Isolates in Pakistan - Ahmed, Zaheer; Inayat, S.; Naeem, K.; Malik, S.A. (International Journal of Poultry Science, 2003)
A comparative study was undertaken to evaluate immune response against four types of infectious bursal disease (IBD) vaccines in broilers. The decline pattern of maternal antibody titres in unvaccinated chicks was compared with those given IBD vaccines, following different vaccination schedules. Indirect ELISA as well as challenge with field virus evaluated the immune response of these vaccines. The results indicated that immune response against different vaccines varied in accordance with the vaccine schedule and levels of maternal antibody against IBDV in the chicks. The challenge studies indicated that only those birds stayed refractory to the challenge in which either sufficient IBDV maternal antibody titres were present or the birds were challenged at least 2 weeks post IBDV vaccination, providing sufficient time for developing an effective immune response. So it is suggested to devise IBD vaccination schedule in the light of prevailing maternal antibody tires in day-old chicks of each flock.